Renal outcomes following fundus fluorescein angiography in patients with diabetic nephropathy: Incidence, risk factors and three‐month kidney function changes - Hakan Ozer; Hafize Irem Demir; Sermin Coban; Gokhan Atay; Yasin Ozturk (Diabetic Medicine, 2026)
Abstract Aims The aim of this study was to determine the incidence of contrast‐associated acute kidney injury (CA‐AKI) after fundus fluorescein angiography (FFA) in a high‐risk diabetic nephropathy (DN) population, to identify clinical predictors of renal injury and to evaluate the effect of acute exacerbation on 3‐month eGFR changes. Methods This retrospective cohort study included 307 patients diagnosed with DN. CA‐AKI was defined as an increase of ≥0.3 mg/dL in serum creatinine level within 48 h or ≥1.5‐fold increase within 7 days after FFA exposure. Patients' medication history and 3‐month post‐procedure eGFR values were recorded. Independent factors predicting CA‐AKI development were assessed using multivariate logistic regression, while long‐term losses were evaluated using linear regression and ROC analysis. Results CA‐AKI occurred in 5.2% of patients. Lower baseline eGFR and diuretic use were independent predictors of CA‐AKI. ROC analysis identified a baseline eGFR threshold of ≤32 mL/min/1.73 m 2 for increased CA‐AKI risk, and a combined model including eGFR and diuretic use demonstrated superior predictive accuracy. Although SGLT‐2 inhibitor use was associated with CA‐AKI in univariate analysis, it was not independently significant after adjustment. Notably, 13 of 16 patients (81.3%) who developed CA‐AKI experienced persistent eGFR decline at 3 months, and CA‐AKI was the strongest predictor of subsequent renal function deterioration. Conclusions FFA is associated with a clinically meaningful risk of CA‐AKI in patients with advanced DN, particularly in those with eGFR ≤32 mL/min/1.73 m 2 and concurrent diuretic therapy. Careful pre‐procedural risk stratification, individualized hydration and post‐procedure renal monitoring are warranted.